Diagnostics and treatment: On the division of labor between primary care physicians and specialists - Malte Griebenow; Mathias Kifmann (University of Hamburg, Hamburg Center for Health Economics (HCHE), 2021)
This paper analyzes the referral processes between a gatekeeping primary-care physician (PCP) and a specialist. Specialists provide superior treatment for some patients but are more costly than PCPs. Agency problems arise because diagnostic signals are private information of the physicians. Welfare optimizing contracts can call for a markup either to the PCP for treatingpatients without referral or to the specialist for referring patients back to the PCP. If the benefit of specialist treatment is uncertain, small markups for the specialist enhance welfare compared to a cost-based fee-for-service contract. Additionally, we consider how waiting costs for referrals affect our main results.
Keywords: 330